KONTEN ‘MARRIAGE IS SCARY’ DI MEDIA SOSIAL DAN IMPLIKASINYA TERHADAP KRITERIA MAHASISWA STDI DALAM MEMILIH PASANGAN - Farhan Akbar Pangestu; Akhmad Husaini (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The "Marriage is Scary" phenomenon on social media reflects the young generation's collective anxiety regarding marriage due to negative narratives of domestic violence and economic instability. This study aims to analyze the implications of this phenomenon on the transformation of partner selection criteria among STDI Imam Syafi’i Jember students from the perspective of the sociology of Islamic law. Employing a qualitative method with thematic analysis, data were collected through in-depth interviews and digital content documentation. The findings reveal that student responses vary across a spectrum ranging from resistance based on religious literacy to increased rational caution. Digital fear narratives drive a shift toward more selective standards, where emotional maturity and the trait of qana’ah (contentment) are now prioritized alongside ritual piety. The concept of kafa’ah has expanded in meaning to include psychological compatibility and financial vision as strategies for conflict risk mitigation. This study concludes that integrating Sharia understanding with psychological readiness functions as a crucial filter in transforming fear into mature readiness, emphasizing the urgency of a pre-marital guidance curriculum adaptive to digital era challenges.